Mechanisms of Lipid Droplet Accumulation in Steatotic Liver Diseases - Dempsey, Joseph L.; Ioannou, George N.; Carr, Rotonya M. (Seminars in Liver Disease, 2023)
The steatotic diseases of metabolic dysfunction-associated steatotic liver disease (MASLD), alcohol-associated liver disease (ALD), and chronic hepatitis C (HCV) account for the majority of liver disease prevalence, morbidity, and mortality worldwide. While these diseases have distinct pathogenic and clinical features, dysregulated lipid droplet (LD) organelle biology represents a convergence of pathogenesis in all three. With increasing understanding of hepatocyte LD biology, we now understand the roles of LD proteins involved in these diseases but also how genetics modulate LD biology to either exacerbate or protect against the phenotypes associated with steatotic liver diseases. Here, we review the history of the LD organelle and its biogenesis and catabolism. We also review how this organelle is critical not only for the steatotic phenotype of liver diseases but also for their advanced phenotypes. Finally, we summarize the latest attempts and challenges of leveraging LD biology for therapeutic gain in steatotic diseases. In conclusion, the study of dysregulated LD biology may lead to novel therapeutics for the prevention of disease progression in the highly prevalent steatotic liver diseases of MASLD, ALD, and HCV.
Keywords: steatotic liver disease; lipid droplet; lipid droplet proteins; perilipins; MASLD; alcohol-associated liver disease; hepatitis C